2012
DOI: 10.1007/s10310-011-0276-3
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing analysis of forest damage by selection logging in the Kabaung Reserved Forest, Bago Mountains, Myanmar

Abstract: Selection logging is a principal management scheme in natural teak-bearing forests in Myanmar. Monitoring the spatial extent and intensity of selection logging is important for sustainable forest management. This study applied the normalized difference vegetation index (NDVI) image differencing method using two SPOT-5 pan-sharpened images (2.5 m spatial resolution) taken in October 2007 and January 2009 to analyze canopy changes associated with damage from forest harvesting. According to the pixel-based analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The trial and test approach was also used in forest management for clear-cuts and regrowth detection in temperate forest ecosys- tems (Banner & Lynham 1981, Hayes & Sader 2001, and for the identification of selective logging (Win et al 2012). Sepehry & Liu (2006) used symmetric threshold identification by testing threshold values ranging between 1·σ and 2·σ to monitor land cover change induced by flood, while Sarp (2012) used 1·σ threshold to detect vegetation change and main environmental effects of surface mining activities.…”
Section: Resultsmentioning
confidence: 99%
“…The trial and test approach was also used in forest management for clear-cuts and regrowth detection in temperate forest ecosys- tems (Banner & Lynham 1981, Hayes & Sader 2001, and for the identification of selective logging (Win et al 2012). Sepehry & Liu (2006) used symmetric threshold identification by testing threshold values ranging between 1·σ and 2·σ to monitor land cover change induced by flood, while Sarp (2012) used 1·σ threshold to detect vegetation change and main environmental effects of surface mining activities.…”
Section: Resultsmentioning
confidence: 99%
“…While there is no detailed estimate of the illegal logging intensity in this region, several studies implied that illegal logging activities caused severe forest losses [14,15]. Shifting cultivation has also been conducted by indigenous people since the 19th century [16]. [46] was used to define the country borders.…”
Section: Study Areamentioning
confidence: 99%
“…In 2016, in response to the forest loss, the Myanmar government banned logging activities for one year throughout the entire country and for 10 years in specific regions. However, it is unclear whether the ban will effectively reduce forest loss, as previous studies have shown that disturbance agents other than logging, such as dam construction and shifting cultivation, play an important role in deforestation in Myanmar [14][15][16][17]. Thus, the attribution of disturbance agents and the quantification of areas affected by disturbance agents must be characterized in a consistent manner to obtain accurate information.…”
Section: Introductionmentioning
confidence: 99%
“…NDVI was one of the most successful of many attempts to simply and quickly identify vegetated areas and their »condition,« and it remains the best-known and most-used index for detecting live green plant canopies in multispectral remote sensing data (Fuller 2006;Milanović et al 2008;Campbell and Wynne 2011;Ne Win et al 2012). NDVI also has the advantage of allowing comparisons between images acquired at different times (Lillesand et al 2004).…”
Section: Introductionmentioning
confidence: 99%